Slovosloženije v "pletenii sloves" - Vidmarović, Natalija (Array, 1996)
In this article the author deals with problems considering compound words, used in the works of medieval hagiographs. The author analyzes mostly compound adjectives and nouns from the point of basic word component and from descriptive component. The author also considers the function of compound words in the frame of "pletenije sloves".